Comparing Traditional‐Residential, Personalised Residential and Personalised Non‐Residential respite services: Quality of life findings from an Irish population with mild–moderate intellectual disabilities. (28th September 2018) - Nicholson, Emma; Guerin, Suzanne; Keogh, Fiona; Dodd, Philip
Accessible Summary: This study looked at differences between three types of respite care for people with intellectual disabilities. The three types of respite care were: 1) an overnight stay in a residential facility, 2) an overnight stay, where the person could choose where they stayed and what they did during their time in respite care, and 3) a non‐overnight service where people were supported to choose what they wanted to and who they wanted to spend time with in respite care. Where people using respite care had a choice as to how they spent their time they were reported to have higher levels of emotional well‐being, personal development, rights and interpersonal relationships. These results are important because they show that giving people choice in how they spend time in respite care might have better outcomes than Traditional‐Residential forms of respite care. Abstract: Background: Respite care is an essential support for people with intellectual disabilities and their families; however, there is limited evidence examining different models of respite care. The present research examined quality of life among adults with intellectual disabilities using three different models of respite services in Ireland. Method: A quasi‐experimental research method was adopted, which sought to determine differences in quality of life across the three respite care groups using two measures, 1) a self‐reported quality of life scale and 2) a quality of life questionnaire filled out by a keyworker. Participants were people with mild/moderate intellectual disabilities ( n = 82) and their keyworkers ( n = 81). Results: Three distinct models of respite services were assessed: (a) Traditional‐ Residential respite; (b) Personalised Residential respite, and (c) Personalised Non‐Residential respite. No differences emerged between the groups on self‐reported quality of life; however, the groups differed on a proxy measure of quality of life with respect to Rights, emotional well‐being, personal development and interpersonal relationships. Conclusion: The current data offer an initial exploration of self‐ and proxy‐reported quality of life among persons with intellectual disabilities in receipt of novel models of respite care in Ireland.